صحاح ستہ میں وارد نعتیہ شاعری کا تحقیقی مطالعہ: The Research study of praising verses of Prophet Muhammad ﷺ in Siha-e-Sittah - Saeed-Ur-Rehman, Dr. Muhammad; Bilal , Muhammad (Al-Amīr Research Journal for Islamic Studies, 2023)
“Naat” is a part of poetry which refer to praising and admiration of Prophet Muhammad ﷺ the present study describes those Poetic verses which are in the six authentic books of Hadith. These Naat’s were written by Hassān Bin Thābit, Abdullah bin Rawaha, Abdu Talib, Girls of Banu Najar and different sahabahرضوان اللہ علیھم اجمعین . Keywords: Naat, Praising, Admiration, Hassān Bin Thābit, Poets.